1980
DOI: 10.1113/jphysiol.1980.sp013079
|View full text |Cite
|
Sign up to set email alerts
|

Release of calcium ions linked to the activation of potassium conductance in a caffeine‐treated sympathetic neurone.

Abstract: SUMMARY1. The mechanism of spontaneous and rhythmic hyperpolarizations which occur in bullfrog sympathetic ganglion cells under the effect of caffeine (2-10 mM) were further analysed.2. Intracellular injection ofEGTA blocked generation of caffeine hyperpolarizations (C-hyperpolarizations): this confirmed the previous conclusion (Kuba & Nishi, 1976) that these hyperpolarizations are caused by rhythmic increases in the K+ conductance (GK) of the membrane as a result of rises in free intracellular Ca2+.3. The amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
120
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(129 citation statements)
references
References 39 publications
9
120
0
Order By: Relevance
“…4D) and Ca 2ϩ -free solution (Fig. 4E), possibly reflecting a requirement for Ca 2ϩ influx in the activation of the CICR mechanism in neurons (42,43). Thapsigargin, a SERCA inhibitor, depleted the ER (34) as revealed by a slow [Ca 2ϩ ] i transient (Fig.…”
Section: Mt-acting Drugs Change Cytosolic and Mitochondrialmentioning
confidence: 99%
“…4D) and Ca 2ϩ -free solution (Fig. 4E), possibly reflecting a requirement for Ca 2ϩ influx in the activation of the CICR mechanism in neurons (42,43). Thapsigargin, a SERCA inhibitor, depleted the ER (34) as revealed by a slow [Ca 2ϩ ] i transient (Fig.…”
Section: Mt-acting Drugs Change Cytosolic and Mitochondrialmentioning
confidence: 99%
“…Ryanodine receptors are selectively modulated by and named after a plant alkaloid that blocks the channel at high concentrations (Ͼ100 M) and locks the channel in an open subconductance state at lower concentrations (Fill and Coronado, 1988). On the basis of a sensitivity to ryanodine and other modulators of C a 2ϩ stores, it has been suggested that CICR plays a role in a number of neuronal processes, including cell excitability (Kuba, 1980;Currie and Scott, 1992), neurotransmission (Peng, 1996), cell development and differentiation (Holliday et al, 1991;Gomez et al, 1995), and synaptic plasticity (Obenaus et al, 1989;Reyes and Stanton, 1996;Wang et al, 1996). Although functional ryanodine-sensitive stores are present in neurons and seem to participate in physiological processes, it is not clear how the stores contribute functionally to Ca 2ϩ signaling.…”
Section: Camentioning
confidence: 99%
“…Nucleotide residue 15230 is followed by a poly(dA) tract. The 5'-terminal residue of the sequence carried by each cDNA clone from brain libraries is indicated by filled circle (see section 2.2); the marks for the cDNA clones IBRRZ, 3,4,6,313 and 319 are omitted. The boundaries where the cDNA sequence is interrupted by introns in genomic DNA are shown by arrows; four exon-intron boundaries were determined in this study.…”
Section: Characterization Of the 24-kb Rna In Brainmentioning
confidence: 99%